Line x tester analysis for combining ability in okra [Abelmoschus esculentus (L.) Moench.] (Indian Journal of Arid Horticulture, 2025)
Combining ability effects were estimated for different characters in a line x tester crossing programme comprising 45 hybrids produced by crossing of 15 lines and 3 testers. Parents and hybrids differed significantly for gca and sca effects, respectively. High average degree of dominance revealed predominance of non-addiive gene effects for all the traits. The parents Swati-10, Heritage green, Punjab Padmini, Ankur-40, VRO-6 and Arka Anamika were good general combiner for majority of characters in various environments. Therefore, these lines can be used for hybridization for producing promising recombinants. This indicates that parent showing high gca for fruit yield per plant might be due to high gca for fruit weight, fruit length, fruit girth and number of fruits per plant. High sca effects were reported for cross combinations, BO-3 x Arka Anamika in E,, Swati-10 x Parbhani Kranti and heritage Green x Arka Abhay in E, and BO-3 x Parbhani Kranti in E, environment Key words: Combing stability, Line, Tester, Gca effects, Sca effects, Gene effects, Non-additive, Dominance, parents and Hybrids.
Keywords: Anamika; Parbhani Kranti